Semi-analytical solutions and comparative study of Shehu HPM and Elzaki HPM methods in Jeffery-Hamel fluid flow problem (Nonlinear Studies, 2025)
The present study introduces the Shehu and Elzaki Homotopy perturbation methods as reliable techniques for solving the Jeffery-Hamel flow. Both methods are utilized to validate and compare solution profiles for the Jeffery-Hamel fluid flow problem under consideration. The series solution findings demonstrate that these techniques are computationally efficient and straightforward to implement. MATLAB is employed to graphically display the semi-analytical solutions, revealing excellent agreement between the solution profiles generated by both approaches. Furthermore, it is observed that for a fixed Reynolds number, the solution profile increases as ? transitions from negative to positive values. Similarly, increasing Reynolds numbers for a fixed  results in higher solution profiles. Such proposed techniques are good alternate for numerical techniques and analytical techniques.